PENGARUH PENDAPATAN PEREMPUAN TERHADAP KEMISKINAN DAN KETIMPANGAN PENDAPATAN: BUKTI DATA PANEL DI ACEH - Ikhsan; Zulkifli (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study analyzes the effect of women’s income on poverty and income inequality. Using panel data from 23 districts in Aceh during the 2010-2020 period, the fixed-effect approach panel regression was applied as a data analysis model. An important finding of this study is that women’s income can significantly reduce poverty levels. The greater the contribution of women’s income in the household, the lower the poverty rate. However, the women’s income also significantly adversely affects the income distribution. The higher the women’s income, the higher the inequality.